Mathematically Gifted Accelerated Students Participating in an Ability Group: A Qualitative Interview Study - Smedsrud, Jørgen (Frontiers in Psychology, 2018)
Schools in Norway often emphasize heterogeneous groups in education. The postulated negative effects of homogeneous ability groups on motivation and academic self-concept have long been debated. This study uses semi-structured interviews to investigate how a group of eleven accelerated and ability-grouped high-ability students (gifted) in math have experienced school. All students were interviewed individually. This study explores categories connected to the students’ motivation for the subject, challenges in school, peer and teacher relationships and academic self-concept. The aim of the study is to investigate whether the school system is able to provide an adequate learning environment for high-ability students, both in ordinary class and in ability groups. The findings show that although some of the needs of high-ability students in Norway are being met, there is much work to be done before an optimal learning environment is established for these students. For example, students do not receive sufficient challenges in math. Furthermore, teachers in the early years of school lack sufficient mathematical knowledge to challenge and support mathematically gifted students, students’ motivation for the subject is lower than expected, and boys’ self-concept seems to be higher than that of girls.